Network Security Analysis in Internet of Things (IoT) Systems - Nova Oktapiana; Dirja Nur Ilham; Fardiansyah Fardiansyah; Depi Ginting; Fera Anugreni (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
The rapid development of the Internet of Things (IoT) has significantly transformed various sectors, including industry, healthcare, smart cities, and agriculture. However, this growth has also increased the complexity and scale of network security vulnerabilities. IoT devices are typically resource-constrained and operate in heterogeneous network environments, making them attractive targets for cyberattacks. This study aims to analyze key network security challenges in IoT systems, evaluate solution technologies proposed in recent literature, and formulate evidence-based recommendations for improving IoT security. The research adopts a Systematic Literature Review (SLR) method by examining ten peer-reviewed articles published between 2020 and 2023 and indexed in IEEE Xplore, SpringerLink, and ACM Digital Library. The results indicate that major IoT security challenges include vulnerabilities in communication protocols, limited computational and energy resources, and the increasing prevalence of attacks such as Distributed Denial of Service (DDoS), spoofing, and ransomware. The most frequently proposed solutions involve machine learning-based anomaly detection, lightweight cryptographic mechanisms, layered security architectures using edge–fog–cloud computing, and blockchain integration to enhance authentication and data integrity. This study concludes that IoT security requires a holistic and multidisciplinary approach that integrates multiple complementary technologies within a unified security framework.